Local variation in the use of out-of-home care in England: analysis of linked administrative data: IJPDS (2017) Issue 1, Vol 1:245 Proceedings of the IPDLN Conference (August 2016) - McGrath-Lone, Louise; Harron, Katie; Dearden, Lorraine; Nasim, Bilal; Gilbert, Ruth (International Journal of Population Data Science, 2017)
ABSTRACT Objectives In England, approximately one in thirty children spend time in out-of-home care (OHC) by age 18.Use of OHC is known to vary across the country, which may be explained in part by ethnic group differences in the risk of being placed in OHC. This study uses linked administrative data to determine whether local variation in the cumulative proportion of children placed in OHC is explained by differences in the ethnic distribution of the local populations. Approach Administrative social care records from January 1, 1992 to December 31, 2012 for a one-third sample of children were linked to publicly-available local authority population estimates. Two artificial birth cohorts were selected for analysis; 1992-94 and 2009-11. The cumulative proportion of children who entered OHC was calculated for each of the current 150 local authorities (the local government bodies who deliver children’s social care services). Funnel plots were used to identify local authorities with higher or lower than expected rates of entry to OHC, taking into account the size of their child population and its ethnic distribution. Results Overall 3.3% of children in England born 1992-94 had entered OHC by age 18. Rates varied considerably by local authority from this national average, ranging from just 1.0% in Rutland to 6.9% in Manchester (both p<0.001). Local authority variation in rates of entry to OHC was also evident among the most recent birth cohort: while 0.8% of children born 2009-11 had entered OHC by age one, this figure varied from 0.2% in Rutland to 2.7% in Blackpool (p<0.05 and p<0.001 respectively). Indirect standardisation of rates for ethnicity did not appreciably change the cumulative percentage of children entering care in each local authority or the relative rankings of local authorities. Conclusion There is considerable, persistent variation between local authorities in England in the rate of entry into OHC during childhood which cannot be attributed to differences in ethnic composition. Further linkage of administrative social care data to area-level data (for example, related to social care spending or indicators of social deprivation) would be useful for understanding local variation in thresholds for placing a child in OHC.